Pharmacokinetic Study of Amoxicillin Capsule in Healthy Bangladeshi Subjects using Urinary Excretion Data - Ullah, Md Ashik; Azad, Mohammad Abul Kalam; Sultana, Rebeka; Kabir, Eva Rahman; Latif, AHM Mahbub; Hasnat, Abul (Dhaka University Journal of Pharmaceutical Sciences, 2010)
The aim of the study was to compare the urinary excretion data and bioavailability of two 500 mg amoxicillin capsules formulations in healthy Bangladeshi subjects under fasting condition and evaluate the ethnic variations in drug disposition. Twenty-four subjects were enrolled into this single-dose, randomized, open-label, twoway cross over study. A washout period of one week was allowed between two treatments. Following oral administration, urine samples were collected at different time intervals and were analyzed using a validated HPLC method with UV detection. The pharmacokinetic parameters for two formulations were calculated by noncompartmental method using the software Kinetica and statistical analysis was done for the evaluation of bioequivalence. The pharmacokinetic analysis indicated that the kinetic disposition of two formulations was similar. This was evident when the mean (± standard deviation) values of the various pharmacokinetic parameters were compared. No significant difference between two formulations was found when analyzed by paired t-test and ANOVA. Therefore it can be concluded that the test product (SK-mox®) is bioequivalent to the reference product (Amoxil-Bencard®) based on the US FDA's regulatory definition. Moreover, an ethnic variation was observed following 64.34% cumulative urinary recovery of amoxicillin over 12 hours when compared with other studies. Key words: Amoxicillin; pharmacokinetics; Bangladeshi subjects. DOI: 10.3329/dujps.v8i1.5336 Dhaka Univ. J. Pharm. Sci. 8(1): 53-59, 2009 (June)